Preventive effect of Terminalia bellirica (Gaertn.) Roxb. extract on mice infected with Salmonella Typhimurium - Kong, Qinghui; Shang, Zhenda; Liu, Yao; Fakhar-e-Alam Kulyar, Muhammad; Suo-lang, Sizhu; Xu, Yefen; Tan, Zhankun; Li, Jiakui; Liu, Suozhu (Frontiers in Cellular and Infection Microbiology, 2023)
Terminalia bellirica (TB) is a traditional herbal combination used in Chinese medicine for the treatment of a broad range of diseases. Based on its digestive characteristics, intestinal physical and immunological barrier and gut microbiota effects, we investigated its extract in the mice model. Results show that the extract could improve the serum immunoglobulins (IgA and IgG), decrease the intestinal cytokine secretion to relieve intestinal cytokine storm, reinforce the intestinal biochemical barrier function by elevating the sIgA expression and strengthen the intestinal physical barrier function. Simultaneously, based on the V3 – V4 region of the 16S rRNA analysis, results of the taxonomic structure of the intestinal microbiota demonstrated that the TB prevention effect transformed the key phylotypes of gut microbiota in S. Typhimurium-challenged mice and promoted the multiplication of beneficial bacteria. Furthermore, the abundance of Firmicutes and Deferribacteres increased, whereas that of Bacteroidetes and Actinobacteria decreased. At the genus level, the abundance of Ruminococcus and Oscillospira was substantially enhanced, whereas the other dominant genera showed no significant change between the vehicle control groups and TB prevention groups. In summary, these results provide evidence that the administration of TB extract can prevent S. Typhimurium infection by alleviating intestinal physical and immunological barriers and normalising the gut microbiota, highlighting a promising application in clinical treatment. Thus, our results provide new insights into the biological functions and therapeutic potential of TB for the treatment of intestinal inflammation.